Effect of co‐culture with intact embryos on development of bovine separated blastomeres. (9th January 2013) - Nagai, Makoto; Hori, Noboru; Miyamoto, Michiko; Sakaguchi, Masanobu; Hayakawa, Yuji; Kawai, Megumi; Kita, Mitsuo; Furuya, Tetsuya; Imai, Kei
Abstract To improve embryo development in bovine separated blastomeres, we evaluated applicability of co‐culture with intact embryos. The morphological quality of blastocysts derived from separated blastomeres and rate of blastocyst formation were only slightly increased when the cells were co‐cultured with intact embryos, which did not provide significant differences when statistically analyzed. However, the cell count of inner cell mass (ICM), trophectoderm (TE) and total number of cells in Day 8 blastocysts were significantly higher when the cells were co‐cultured with the intact embryos than those with the cells cultured individually (P < 0.05). Transfer of four monozygotic pairs of blastocysts derived from the cells co‐cultured with intact embryos led to three pregnancies even when the blastomeres were produced by in vitro maturation and in vitro fertilization of oocytes collected by ovum pick‐up from elite cows. These results suggest that co‐culturing with intact embryos may enhance development of bovine separated blastomere.